Evaluation of Straight Karanja Oil (Pongamia Pinnata) as a Compatible Fuel for Compression Ignition Engines - Tiwari, Kamta Prasad; Singh, Ram Narayan (The Nucleus, 2025)
The increasing energy demands, depletion of traditional energy sources, and significant environmental changes have necessitated the search for alternatives to petroleum fuels. Among the available alternatives, straight vegetable oil (SVO) is a viable option due to its properties being similar to fossil diesel (FD). This study shows that the viscosity of straight Karanja oil significantly decreases and aligns with FD when heated to temperatures between 105°C and 110°C. The viscosity of Karanja oil was reduced using a specially developed coiled-type heat exchanger to recover waste heat from engine exhaust flue gas. A compression ignition (CI) engine was operated at a constant speed (1,500 rpm) under varying loads from 10% to 100% of engine rated capacity in 10% increments. While FD exhibited superior performance due to its lower viscosity, heating Karanja oil to 105°C reduced its viscosity, enhancing engine performance However, the brake thermal efficiency (BTE) was poor and brake-specific fuel consumption was higher when using heated Karanja oil compared to FD. Preheated straight Karanja oil (PSKO) showed better performance as compared to unheated straight Karanja oil (USKO). The highest BTE for all tested fuels was recorded at 80% of the engine’s rated load. Although NOx concentration was lower in USKO than FD, however, when PSKO was used, NOx emissions started increasing while CO emissions were decreased. the best diesel engine performance and the lowest emission levels were achieved with Karanja oil heated at 105°C.